PENDAMPINGAN PEMBUATAN MEDIA PEMBELAJARAN PENJAS DI SD. INPRES TAMAMAUNG II KOTA MAKASSAR - Hasmawaty Hasmawaty; Muhammad Zulfikar; Andi Atssam Mappanyukki; Nurul Fadilah Aswar (KORSAcs: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service program is to increase the knowledge and skills of teachers and prospective teachers in making learning media that are not available at school. The service activities were carried out by the author in collaboration with students of the PE Study Program at Megarezky University. The main problem of partners is the limited learning media for athletic sports, namely relay running and hurdling. The purpose of this activity is the availability of learning media that is in accordance with the needs and developmental characteristics of school-age children. This mentoring method consists of the stages of analyzing partner needs, media making assistance and evaluation. The results of the assistance obtained that the media produced were declared practical by Physical Education practitioners so that they were suitable for use by elementary school students. After evaluating the use of media on 27 students of class VI elementary school, it was found that 21 students (77.77%) could use the media well, and 6 students (22.22%) still needed further enrichment and assistance from the teacher (moderate category).